2006
DOI: 10.1021/ja0617690
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic Coupling in Hexanuclear Gadolinium Clusters

Abstract: The magnetic susceptibilities of hexanuclear gadolinium clusters in the compounds Gd(Gd6ZI12) (Z = Co, Fe, or Mn) and CsGd(Gd6CoI12)2 are reported and subjected to theoretical analysis with the help of density functional theory (DFT) computations. The single-crystal structure of Gd(Gd6CoI12) is reported here as well. We find that the compound with a closed shell of cluster bonding electrons, Gd(Gd6CoI12), exhibits the effects of antiferromagnetic coupling over the entire range of temperatures measured (4-300 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 41 publications
(71 reference statements)
1
42
0
Order By: Relevance
“…In this context, oxo, hydroxo and fluorido bridged lanthanide clusters are worthy of note. [24][25][26][27][28][29][30][31] It has been well documented that lanthanide compounds have relevance to homogeneous catalysis, [32] molecule-based magnetic materials, [33] contrast agents for magnetic resonance imaging [34] and fixation media for essential atmospheric gases. [35] In the field of oxidative catalytic transformations, [36] epoxidation of alkenes is a key chemical process in biology, [37] synthetic organic chemistry and in chemical industry.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, oxo, hydroxo and fluorido bridged lanthanide clusters are worthy of note. [24][25][26][27][28][29][30][31] It has been well documented that lanthanide compounds have relevance to homogeneous catalysis, [32] molecule-based magnetic materials, [33] contrast agents for magnetic resonance imaging [34] and fixation media for essential atmospheric gases. [35] In the field of oxidative catalytic transformations, [36] epoxidation of alkenes is a key chemical process in biology, [37] synthetic organic chemistry and in chemical industry.…”
Section: Introductionmentioning
confidence: 99%
“…Observe that the V-[Mn@Sn 12 ] 2 isomer is predicted to be a metastable dimer, while both the E- Sn 12 superexchange coupling is effectively precluded. [35] Consequently, we consider the magnetic exchange coupling of the two magnetic Mn centers. In particular, we focus on the ferromagnetic state (FS), where all the ten 3d electrons (five per each Mn 2 + ) are spin parallel and the antiferromagnetic state (AS) in which all five electrons of one manganese cation are spin up and all five on the other manganese cation are spin down.…”
mentioning
confidence: 99%
“…The amounts of cluster-based electrons (CBEs) are usually obtained by subtracting the numbers of halide ligands from the net valence electron counts of the transition-metal centered rare-earth metal cluster [45]. For instance, applying this scheme to formally distribute electrons in the previously reported Y7I12Co yields a total of 18 CBEs (=7•3 + 9 -12), which is expected to correspond to (preferable) closed-shell configurations for the [TR6]X12R-type compounds [51][52][53]. Further research on the electronic structures of transition-metal centered rare-earth metal cluster halides crystallizing with the [TR6]X10-type whose crystal structure also comprises isolated octahedral [TR6] clusters as observed for the [TR6]X12R-type ( Figure 1) revealed that closed-shell configurations are also achieved The amounts of cluster-based electrons (CBEs) are usually obtained by subtracting the numbers of halide ligands from the net valence electron counts of the transition-metal centered rare-earth metal cluster [45].…”
Section: Tendencies Within Bonding Motifs In Compounds With Polycatiomentioning
confidence: 99%
“…Further research on the electronic structures of transition-metal centered rare-earth metal cluster halides crystallizing with the [TR6]X10-type whose crystal structure also comprises isolated octahedral [TR6] clusters as observed for the [TR6]X12R-type ( Figure 1) revealed that closed-shell configurations are also achieved The amounts of cluster-based electrons (CBEs) are usually obtained by subtracting the numbers of halide ligands from the net valence electron counts of the transition-metal centered rare-earth metal cluster [45]. For instance, applying this scheme to formally distribute electrons in the previously reported Y 7 I 12 Co yields a total of 18 CBEs (=7·3 + 9 -12), which is expected to correspond to (preferable) closed-shell configurations for the [TR 6 ]X 12 R-type compounds [51][52][53]. Further research on the electronic structures of transition-metal centered rare-earth metal cluster halides crystallizing with the [TR 6 ]X 10 -type whose crystal structure also comprises isolated octahedral [TR 6 ] clusters as observed for the [TR 6 ]X 12 R-type ( Figure 1) revealed that closed-shell configurations are also achieved for a total of 18 CBEs (an overview about the [TR 6 ]X 12 R-type as well as [TR 6 ]X 10 -type halides identified to date has been provided elsewhere [54]).…”
Section: Tendencies Within Bonding Motifs In Compounds With Polycatiomentioning
confidence: 99%